2014
DOI: 10.1038/npjpcrm.2014.69
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multiple-dose versus single-dose inhaler devices on COPD patients’ persistence with long-acting β2-agonists: a dispensing database analysis

Abstract: Background:With a growing availability of different devices and types of medication, additional evidence is required to assist clinicians in prescribing the optimal medication in relation to chronic obstructive pulmonary disease (COPD) patients’ persistence with long-acting β2-agonists (LABAs).Aims:To assess the impact of the type of inhaler device (multiple-dose versus single-dose inhalers) on 1-year persistence and switching patterns with LABAs.Methods:A retrospective observational cohort study was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
11
2
Order By: Relevance
“…In 2014 van Boven et al used a Dutch pharmacy dispensing data from 1994 to 2012 in order to analyse LABA persistence in COPD patients. The authors of that study found no significant differences between MDIs and DPIs [30]. We believe the differences observed in our study might be a result of generally lower out-of-pocket costs of MDIs, as compared to DPIs.…”
Section: Discussioncontrasting
confidence: 64%
“…In 2014 van Boven et al used a Dutch pharmacy dispensing data from 1994 to 2012 in order to analyse LABA persistence in COPD patients. The authors of that study found no significant differences between MDIs and DPIs [30]. We believe the differences observed in our study might be a result of generally lower out-of-pocket costs of MDIs, as compared to DPIs.…”
Section: Discussioncontrasting
confidence: 64%
“…In 2014 van Boven et al used a Dutch pharmacy dispensing data from 1994 to 2012 in order to analyse LABA persistence in COPD patients. The authors of that study found no signi cant differences between MDIs and DPIs (30). We believe the differences observed in our study might be a result of generally lower out-of-pocket cost of MDIs, as compared to DPIs.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, we excluded patients who met the following exclusion criteria: (1) Receipt of another antibiotic treatment than doxycycline 3 days before till 7 days after the index date. (2) Age under 55 years, to reduce the chance of including possible asthma patients 30 31. Age was calculated using the difference between index date and birth date.…”
Section: Methodsmentioning
confidence: 99%
“…The following covariates were included as potential confounders: age; gender; frequently used maintenance drugs for COPD treatment within 365 days before index date including SABA, SAMA (short-acting muscarinic antagonist), LABA (ong-acting β agonist), LAMA (long-acting muscarinic antagonist), SABA/SAMA, LABA/LAMA, LABA/ICS (inhaled corticosteroid) and theophylline. Comorbidities in COPD patients were defined on the basis of at least two prescriptions of related drugs within 365 days prior to index date: diabetes (A10), heart failure (C01AA05 or C03C), ischaemic heart disease (C01DA), other cardiovascular disease (C02 or C03 or C07 or C08 or C09, but not for C01AA05, C03C and C01DA), dyslipidaemia (C10), osteoporosis (M05B), anxiety (N05B, N05C), dementia (N06D), depression (N06A), rheumatic arthritis (M01 or M02) and hypothyroid disease (H03) 30…”
Section: Methodsmentioning
confidence: 99%